Temperature control casting process of heat-cracking resistant stainless steel valve body
Patent Information
- Application Number
- CN202611308241.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-16
AI Technical Summary
然而,奥氏体不锈钢具有导热系数低、线膨胀系数大的物理特性,在铸造凝固过程中极易因热应力集中而产生裂纹缺陷,特别是在壁厚差异显著的阀体法兰根部与中腔连接区域,热裂问题普遍存在,对产品质量稳定性构成持续影响;
1、该抗热裂不锈钢阀体的温控铸造工艺中,采用铪和钇改性晶界融合剂与铌钛复合微合金化相结合的晶界净化-微合金化协同处理手段,使钢液中的有害元素在高温下以高熔点化合物形式上浮去除,同时铌钛碳氮化物在凝固前沿形成弥散形核质点以细化铸态组织,钇则在晶界处形成溶质拖曳效应并降低晶界界面能,具有从材料本源上消除晶界弱化诱因的效果,解决了奥氏体不锈钢因杂质元素在晶界偏聚形成低熔点液相而诱发热裂纹的根源性问题,有效提高了铸件的高温凝固抗裂能力,不仅改善了晶界区域的纯净度,还通过细化晶粒和增强晶界结合力提升了铸件的综合力学性能,从而从材料本源层面削弱了热裂的发生条件。
Smart Images

Figure CN122918418A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of casting technology, and more specifically, to a temperature-controlled casting process for a hot-crack resistant stainless steel valve body. Background Technology
[0002] Currently, austenitic stainless steel is widely used in the production of valve castings. Due to its excellent corrosion resistance and good comprehensive mechanical properties, this material is used in the manufacture of medium and high pressure valves in the petroleum, chemical and nuclear power industries. However, austenitic stainless steel has the physical properties of low thermal conductivity and high coefficient of linear expansion. During the casting and solidification process, it is very easy to generate crack defects due to thermal stress concentration. In particular, thermal cracking is common in the valve body flange root and cavity connection area where the wall thickness difference is significant, which has a continuous impact on the stability of product quality. In existing technologies, to improve the filling quality, there are reports of using a stepped gating system in conjunction with chills and risers, or controlling the content of impurity elements to reduce grain boundary segregation. However, considering the structural characteristics of austenitic stainless steel valve castings with large wall thickness differences and concentrated solidification shrinkage stress, there are still some shortcomings in actual production. For example, conventional stepped gating mostly relies on gravity or empirical time to control the opening timing of each layer of ingate, making it difficult to make a precise response based on the actual temperature of the molten steel, which can easily cause local overheating or turbulent gas entrapment during the filling process. While a single impurity control measure can reduce the risk of grain boundary embrittlement, it cannot eliminate the influence of the temperature gradient caused by the casting structure itself. This not only reduces the controllability and stability of the process, causing obstructed feeding channels and uneven stress distribution, but also affects the uniformity of the temperature field during the solidification process of the casting. It also reduces the feeding efficiency of risers for thick parts, leading to the coexistence of internal shrinkage porosity and surface cracking tendency, thereby reducing the first-pass yield and the economy of mass production.
[0003] Therefore, there is an urgent need for a temperature-controlled casting process for stainless steel valve bodies that are resistant to thermal cracking. Summary of the Invention
[0004] The purpose of this invention is to provide a temperature-controlled casting process for a thermally crack-resistant stainless steel valve body to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides a temperature-controlled casting process for a thermally crack-resistant stainless steel valve body, comprising the following steps: S1. Raw material preparation and grain boundary purification-microalloying synergistic treatment: Austenitic stainless steel scrap and alloy furnace charge are prepared and melted in an electric arc furnace. After being transferred to an LF refining furnace, low-sulfur covering slag is used and bottom-blown argon gas is used for deep desulfurization to make the sulfur content of the molten steel ≤0.003%. Then, at the end of the refining process, a modified grain boundary fusing agent is added, and the mixture is heated to 1580-1620℃ and held for 5-8 minutes to allow the active components in the fusing agent to fully diffuse to all parts of the molten steel. Then, a composite microalloying agent and rare earth elements are added, and after being stirred evenly with bottom-blown argon gas, the steel is tapped to obtain molten steel that has undergone grain boundary purification and microalloying synergistic treatment. S2. Mold and Crack-Resistant Structure Preparation and Molding Core Making: Based on the hot spot location and size obtained from the solidification simulation of the three-dimensional model of the valve body, conformal external chills are set on the outer side of the cavity corresponding to the flange root and the thick part of the valve seat, and side chills are set between adjacent insulation risers. Crack-resistant process tie rods are added at the corners where the wall thickness changes abruptly, so as to use the cooling effect of the external chills to make the thick part solidify first and use the tie rods to share the shrinkage stress. At the same time, furan resin sand molding is used, and the cavity surface is coated with alcohol-based zircon powder coating containing nano-zirconia micro powder. Thermocouple mounting holes are reserved on the side of the blockage point of each layer of the vertical runner. S3. Smelting and Filtration: After primary refining in an electric arc furnace, the treated molten steel is transferred to an LF refining furnace and tapped at a temperature of 1600-1630℃ and then transferred to a ladle. During the tapping process, a final deoxidizer is added with the steel stream to perform final deoxidation, so that the hydrogen content of the molten steel is ≤2ppm. A foam ceramic filter is installed in the horizontal runner at a distance of 150-200mm from the center line of the vertical runner. When the molten steel flows through the filter, the oxide inclusions and deoxidation products are intercepted and adsorbed, and pure molten steel is obtained to enter the mold cavity. S4. Stepped temperature-controlled casting: A multi-layer stepped bottom casting system is used for layered casting. Each layer of the horizontal runner entrance is equipped with a ceramic plug and a feedback execution component consisting of a liquid level sensor, a K-type thermocouple and an electric push rod. The liquid level sensor is used to trigger the opening command of the corresponding layer of the horizontal runner. The K-type thermocouple collects the actual temperature of the molten steel at the blockage point of the layer and compares it with a set threshold to verify the opening condition. After the PLC controller judges the condition, it drives the electric push rod to execute the exit or hold of the ceramic plug, forming a layered independent closed-loop control of liquid level triggering, temperature verification and electric execution. S5. Heat preservation, gradient cooling and annealing before hot cutting: After casting, heat preservation cotton is covered on the surface of the sand mold for slow cooling. Then the casting and the sand mold are transferred into the uniform temperature furnace. A differentiated gradient cooling method combining forced air cooling by variable frequency fan in the thick wall area and natural air cooling in the thin wall area is used for cooling. After the sand is removed from the mold, the casting is put back into the furnace for annealing. Then it is cooled to the appropriate temperature in the furnace and then taken out for hot cutting, forming a continuous stress control process that connects gradient cooling, annealing treatment and low temperature hot cutting. S6. Final heat treatment: After hot cutting the riser, the casting is placed in a heat treatment furnace and heated to 1040-1100℃ at a heating rate of ≤200℃ / h and held at that temperature. The holding time is determined according to the maximum wall thickness of the casting, and at least 1.5h for every 25mm of wall thickness. After the holding time, the casting is transferred to circulating water for water quenching to fully dissolve the carbonitrides formed by microalloying and refine the grains. At the same time, the ferrite content is 4-15%, resulting in valve steel castings with resistance to hot cracking and corrosion.
[0006] Furthermore, in S1, the amount of composite microalloying agent added is 0.15-0.40 wt%; the amount of rare earth element added is 0.3-0.5 wt%; the amount of surface-modified grain boundary fusion agent added is 0.05-0.15 wt%; and the balance is austenitic stainless steel scrap and alloy furnace charge.
[0007] Furthermore, the mass ratio of niobium (Nb) to titanium (Ti) in the composite microalloying agent is 8-12:1, which is used to form high-melting-point carbonitrides at the solidification front to refine the as-cast grains; the rare earth element is selected from cerium (Ce) or lanthanum (La), which is used to modify the morphology of inclusions and purify the grain boundaries.
[0008] Furthermore, in S1, the modification of the grain boundary fusion agent includes the following steps: Hafnium (Hf) and yttrium (Y) powders were mixed at a mass ratio of 1:0.5-0.8 and then added to a polyvinyl alcohol (PVA) aqueous solution. The mixture was stirred at 200-400 rpm for 40-60 minutes in a constant temperature water bath at 60-80℃ to uniformly coat the powder surface with a PVA pre-coating. Subsequently, sodium alginate (SA) solution was added and the pH was adjusted to 4.5-5.5. Through hydrogen bonding between PVA and SA, a three-dimensional network structure composite gel coating layer was formed on the powder surface. After centrifugation, the mixture was dried at 80-100℃ for 2-4 hours to obtain grain boundary fusion agent particles with a core-shell structure. These modified particles were then added to an LF refining furnace and thermally decomposed under high-temperature molten steel at 1580-1620℃ and bottom-blown argon stirring conditions, releasing the internal active components of hafnium (Hf) and yttrium (Y). These components then participated in the in-situ chemical reaction in the molten steel as follows: ; ; ; ; In this context, [O] and [S] represent oxygen and sulfur atoms dissolved in molten steel. The HfO2, HfS2, Y2O3, and Y2S3 generated by the reaction are all high-melting-point compounds with melting points above 2000℃ and densities of 4.5-9.0 g / cm³, which are lower than the density of molten steel (7.0-7.8 g / cm³). Therefore, they can float into the slag layer and be removed under the stirring action of bottom-blown argon gas. Yttrium (Y) that does not participate in the deoxidation and desulfurization reaction exists in the austenitic matrix in the form of substitutional solid solution atoms. During solidification, it agglomerates at the grain boundaries. Through its large atomic radius, it forms an elastic strain field near the grain boundaries, reduces the interfacial energy of the grain boundaries, and hinders the non-equilibrium agglomeration of impurity elements to the grain boundaries, thereby achieving the treatment effect of grain boundary purification and enhanced grain boundary bonding.
[0009] Furthermore, in S2, the thickness of the conformal external chill is 0.6-1.0 times the wall thickness of the corresponding hot section, and it is made of gray cast iron or chromite refractory material. A 2-5mm chromite sand buffer layer is placed between the chill and the mold cavity surface. The cross-section of the anti-crack process tie rod is rectangular, the thickness is 0.6-0.8 times the wall thickness of the cavity, and the width of the tie rod is ≥15mm.
[0010] Furthermore, in S2, the nano-zirconia powder in the alcohol-based zircon powder coating accounts for 3-5% of the total mass of the coating, the particle size of the nano-zirconia powder is not greater than 50nm, the coating thickness is 0.3-0.5mm and it is dried by ignition, and the nano-zirconia coating forms a physical isolation layer at the interface between the molten steel and the mold cavity at high temperature to suppress the interface reaction.
[0011] Furthermore, in S3, the heat-insulating riser is a heat-generating heat-insulating riser, the riser modulus is ≥ the maximum thermal section modulus of the valve body × 1.2, and the top of the riser is covered with a heat-insulating covering agent; the thickness of the foam ceramic filter is 15-20mm, and the pore density is 15-20ppi.
[0012] Furthermore, in S4, the opening control of each layer of the horizontal gating system in the multi-layer stepped bottom pouring system includes the following steps: Molten steel is continuously injected into the mold cavity from the bottom inner gating channel, and the molten steel level in the vertical gating channel rises accordingly. When the liquid level sensor detects that the liquid level has risen to the blockage point of the upper horizontal gating channel, the PLC controller reads the real-time temperature value of the K-type thermocouple at the blockage point and compares it with the preset threshold range of 1480-1510℃. If the measured temperature is within the threshold range, the PLC controller sends an opening command to the corresponding electric push rod, which drives the ceramic ball to exit the horizontal runner inlet, and the horizontal runner of that layer opens. If the measured temperature is higher than the upper limit of the threshold, the PLC controller postpones sending the opening command, the electric push rod keeps the ceramic ball in the horizontal runner inlet closed, and the molten steel continues to be injected into the cavity through the lower layer of the already opened ingate. The horizontal runner of that layer will be opened again after the molten steel in the vertical runner cools down to within the threshold range due to heat dissipation. The opening timing of each layer of horizontal runner is controlled independently according to the above logic, and the measured temperature difference between two adjacent layers when they are opened is ≤25℃. By controlling the opening sequence and timing of the above-mentioned layer-by-layer opening, the rising speed of the molten steel surface in the cavity is kept at 10-15 mm / s, and the pouring temperature is kept at 1450-1480℃.
[0013] Furthermore, in step S5, the insulation cotton covering thickness is set at 1 hour for every 25mm of casting wall thickness, allowing the casting to cool slowly to 550-650℃ before being placed in the homogenizing furnace. During the differential gradient cooling process, the temperature difference between the thick and thin wall regions is collected every 30 seconds, and the operation of the variable frequency fan is dynamically adjusted accordingly to ensure that the instantaneous temperature difference between the thick and thin wall regions is ≤80℃. Before opening the mold, the casting is cooled to below 200℃ with the mold, cleaned of sand, and then reheated in the furnace to 600-650℃ for holding. After that, it is slowly cooled to below 350℃ with the furnace before being taken out for hot cutting of the riser. By using gradient cooling to keep the temperature difference between the thick and thin walls ≤80℃, the residual stress is initially homogenized inside the casting. Then, the stress is further released within the toughness temperature window of austenitic stainless steel through annealing treatment at 600-650℃. During hot cutting, the casting temperature has dropped to ≤350℃, reducing the temperature gradient in the hot cutting area.
[0014] Furthermore, the temperature-controlled casting process is applicable to the casting production of gate valve bodies made of DN100-DN400 austenitic stainless steel of ASTM A351 standard CF8, CF8M, CF3 or CF3M.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In the temperature-controlled casting process of this anti-hot crack stainless steel valve body, a grain boundary purification-microalloying synergistic treatment method is adopted, which combines hafnium and yttrium modified grain boundary fusing agents with niobium-titanium composite microalloying. This allows harmful elements in the molten steel to float and be removed at high temperatures in the form of high-melting-point compounds. At the same time, niobium-titanium carbonitrides form dispersed nucleation points at the solidification front to refine the as-cast structure. Yttrium forms a solute dragging effect at the grain boundaries and reduces the grain boundary interface energy. This has the effect of eliminating the grain boundary weakening inducing factors from the material source. It solves the root cause problem of hot cracking induced by the segregation of impurity elements at the grain boundaries to form low-melting-point liquid phases in austenitic stainless steel. It effectively improves the high-temperature solidification crack resistance of the casting. It not only improves the purity of the grain boundary region, but also improves the comprehensive mechanical properties of the casting by refining the grains and enhancing the grain boundary bonding force, thereby weakening the conditions for hot cracking from the material source.
[0016] 2. In the temperature-controlled casting process of this heat-crack resistant stainless steel valve body, by setting a foam ceramic filter in the horizontal runner and implementing deep desulfurization and final deoxidation during the refining stage, oxide inclusions and deoxidation products in the molten steel are effectively intercepted before entering the mold cavity. At the same time, the hydrogen content of the molten steel is kept below 2ppm. This not only avoids the problem of stress concentration caused by inclusions as crack sources in traditional processes, but also reduces microscopic pore defects formed by gas precipitation during solidification. This improves the purity of the molten steel entering the mold cavity, thereby reducing the probability of cracks induced by the coexistence of inclusions and pores at the solidification source.
[0017] 3. In the temperature-controlled casting process of this anti-crack stainless steel valve body, a layered independent closed-loop control method is adopted, which is triggered by a liquid level sensor, calibrated by a K-type thermocouple, judged by a PLC controller, and executed by an electric push rod. This solves the problems in the existing technology where, when there is a deviation between the actual temperature of the molten steel and the preset value, the ingate is still opened according to a predetermined time or liquid level. This results in the premature injection of low-temperature molten steel, forming a solidified shell that hinders feeding, and the premature entry of high-temperature molten steel, causing local overheating and exacerbating the shrinkage difference. At the same time, the segmented control of the pouring temperature is combined with the constraint of the rising speed of the liquid surface in the cavity, so that the molten steel fills the mold layer by layer from bottom to top smoothly, avoiding secondary oxidation and grain coarsening caused by turbulent air entrapment and local overheating. It also matches the opening time of each layer of ingate with the actual temperature field distribution in the cavity, thereby improving the feeding conditions of thick parts, reducing the peak shrinkage stress, and effectively improving the internal density and dimensional stability of the casting. Attached Figure Description
[0018] Figure 1 This is a flowchart of the temperature control casting process for the thermal crack resistant stainless steel valve body of the present invention. Figure 2 This is a comparison chart of the scrap rate of thermal cracking treated by grain boundary purification in this invention; Figure 3 This is a comparison diagram of the shrinkage porosity distribution in the temperature-controlled stepped casting of this invention; Figure 4 This is a comparison diagram of the hot cutting cracks and residual stress in the cooling annealing process of this invention; Figure 5 This is a comparison chart of the complete mechanical properties of the process of this invention. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1: DN250 (10″) gate valve body, material CF8M (ASTM A351) Casting parameters: gross weight 185kg, flange wall thickness 52mm, cavity wall thickness 22mm, maximum hot spot diameter φ65mm.
[0021] according to Figure 1 As shown, the temperature-controlled casting process includes the following steps: S1. Raw material preparation and grain boundary purification-microalloying co-processing: Austenitic stainless steel scrap and alloy furnace charge are added to an electric arc furnace for melting. After melting, the mixture is transferred to an LF refining furnace. Low-sulfur covering slag and bottom-blown argon stirring are used for deep desulfurization treatment to ensure that the sulfur content of the molten steel is ≤0.003%. At the end of refining, a surface-coated modified grain boundary fusion agent containing Hf and Y is added. The mixture is heated to 1580-1620℃ by electrodes and held for 5-8 minutes to allow the active components to fully diffuse. Subsequently, a composite microalloying agent (Nb to Ti mass ratio 10:1, addition amount 0.25wt%) and rare earth element Ce (addition amount 0.04wt%) are added. The mixture is stirred with bottom-blown argon for 5 minutes until the elements are evenly distributed before tapping the steel.
[0022] S2. Mold and Crack-Resistant Structure Preparation and Molding Core Making: Based on the three-dimensional model of the valve body, solidification simulation is performed. According to the distribution of hot spots, conformal external chills (thickness is 0.75 times the wall thickness of the hot spot, material is chromite refractory material, and a 3mm chromite sand buffer layer is placed between the chills and the cavity surface) are set on the outer side of the corresponding cavity at the flange root and the thick part of the valve seat. Side chills are set between adjacent insulation risers. Crack-resistant tie rods (rectangular cross section, thickness is 0.7 times the wall thickness of the cavity, width 18mm) are set at the R-angle of the flange and the cavity. Furan resin sand molding is used. The cavity surface is coated with alcohol-based zircon powder coating containing 4wt% nano zirconium oxide micro powder (particle size ≤50nm), with a coating thickness of 0.4mm and dried by ignition. Thermocouple mounting holes are reserved next to the blocking points of the horizontal runners of each layer of the vertical runner.
[0023] S3. Smelting and Filtration: The treated molten steel is tapped at 1610℃ and transferred to the ladle. During the tapping process, a final deoxidizer is added with the steel stream for final deoxidation. A 15ppi SiC foam ceramic filter (18mm thick) is installed in the horizontal runner at a distance of 180mm from the center line of the vertical runner. When the molten steel flows through the filter, the oxide inclusions and deoxidation products are intercepted and adsorbed.
[0024] S4. Stepped temperature-controlled pouring: A two-layer stepped bottom pouring system is adopted. The lower inner runner is tangentially fed into the valve body. Each horizontal runner entrance is equipped with a ceramic plug and a feedback execution component consisting of a liquid level sensor, a K-type thermocouple, and an electric push rod. The pouring temperature is 1465±10℃. When the molten steel level in the vertical runner reaches the upper blockage point and the temperature measured by the K-type thermocouple drops to 1505℃, the PLC controller drives the electric push rod to retract the ceramic plug and open the upper horizontal runner, controlling the rising speed of the molten steel in the cavity to about 13mm / s, and the filling time is 42s.
[0025] S5. Heat preservation, gradient cooling and pre-hot cutting annealing: After casting, the sand mold surface is covered with heat preservation cotton for 2.5 hours. After cooling to 600℃, it is placed in a uniform furnace for differentiated gradient cooling, with the thick-walled area forced by a frequency converter fan and the thin-walled area naturally cooled by air. The temperature difference is collected every 30 seconds and the fan is dynamically adjusted to keep the temperature difference within 75℃. The casting is cooled to 180℃ with the mold, then the mold is opened and the sand is cleaned. It is then reheated in the furnace to 650℃ and kept for 3 hours. After cooling to 300℃ with the furnace, the riser is cut.
[0026] S6. Final heat treatment: After hot cutting the riser, the casting is placed into a heat treatment furnace and heated to 1060℃ at a heating rate of ≤200℃ / h. After holding for 3 hours, it is transferred to circulating water for water quenching. Ferrite FN≈10%.
[0027] Example 2: DN400 (16″) gate valve body, material CF3 (ASTM A351) Casting parameters: gross weight approximately 420 kg, flange wall thickness 72 mm, cavity wall thickness 28 mm, maximum hot spot diameter φ85 mm.
[0028] The steps of the temperature-controlled casting process are the same as in Example 1, except that: the steel liquid has a carbon content of ≤0.03% (low carbon and controlled nitrogen), the amount of composite microalloying agent added is 0.35wt%, the amount of rare earth elements added is 0.05wt%, and the tapping temperature is 1620℃; the thickness of the conformal external chill is 0.75 times the wall thickness of the hot section (25mm); the pouring temperature is 1455℃; the air cooling intensity of the thick-walled zone in the gradient cooling is increased by one level, and the temperature difference is controlled within 78℃; the annealing holding time is extended to 650℃×5h, and the furnace is cooled to 300℃ before hot cutting; the solution treatment temperature is 1040-1080℃.
[0029] Example 3: DN150 (6″) gate valve body, material CF8 (ASTM A351) Casting parameters: gross weight approximately 95kg, flange wall thickness 38mm, cavity wall thickness 16mm, maximum hot spot diameter φ48mm.
[0030] The steps of the temperature-controlled casting process are the same as those in Example 1, except that: the amount of composite microalloying agent added is 0.20wt%, the amount of rare earth element added is 0.035wt%, the tapping temperature is 1605℃; the thickness of the conformal chill is 0.70 times (14mm) of the wall thickness of the hot section; the pouring temperature is 1460℃; the gradient cooling temperature difference is controlled within 70℃; the annealing temperature is 600℃ and held for 3h, then cooled in the furnace to 320℃ and hot-cut; the solution treatment temperature is 1080℃ and held for 2h.
[0031] Example 4: DN100 (4″) gate valve body, material CF3M (ASTM A351) Casting parameters: gross weight approximately 52kg, flange wall thickness 30mm, cavity wall thickness 12mm, maximum hot spot diameter φ38mm.
[0032] The steps of the temperature-controlled casting process are the same as in Example 1, except that: the amount of composite microalloying agent added is 0.18wt%, the amount of rare earth element added is 0.03wt%, the tapping temperature is 1600℃; the thickness of the conformal chill is 0.70 times (10mm) of the wall thickness of the hot section; there are two φ80mm heat-insulating risers; the pouring temperature is 1450℃; the gradient cooling temperature difference is controlled within 65℃; the annealing temperature is 600℃ and held for 2 hours, then cooled in the furnace to 320℃ and hot-cut; the solution treatment temperature is 1040℃ and held for 1.5 hours.
[0033] Comparative Example 1 The process employs conventional bottom-pouring and insulated riser technology, without temperature-controlled stepped pouring, conformal chills, crack-preventing bracing, or gradient cooling control. Riser is directly hot-cut after opening the mold at room temperature, followed by conventional solution treatment. The specific steps are as follows: The molten steel was prepared according to the chemical composition of ASTM A351CF8M standard, melted in an electric arc furnace and then refined by LF. The tapping temperature was 1610℃, and it was directly poured using a single-layer bottom-pouring gating system at a pouring temperature of 1465℃. A heating and heat-insulating riser was set above the cavity, with the riser modulus being 1.1 times the thermal section modulus. After pouring, the steel was naturally cooled to room temperature, the mold was opened, and the sand was removed. The riser was cut off directly using oxygen cutting. Finally, it underwent water quenching and solution treatment at 1060℃ for 3 hours.
[0034] Comparative Example 2 The casting was prepared using the existing temperature-controlled stepped casting method (CN106955994A): The molten steel was prepared according to the chemical composition of ASTM A351CF8M standard. A two-layer stepped bottom-pouring system was used, with thermocouples installed in the vertical runner to monitor the molten steel temperature in real time. When the temperature of the molten steel in the vertical runner dropped to the preset opening temperature, the corresponding horizontal runner was opened. No liquid level sensor was used for control. Conventional insulated risers were used, without conformal chills or crack-preventing bracing structures. The cooling method was natural air cooling. After the casting cooled to room temperature, it was opened from the mold, and the risers were directly hot-cut. Subsequently, it underwent water quenching and solution treatment at 1060℃ for 3 hours. The remaining process parameters were the same as steps S1 and S3 in Example 1.
[0035] Comparative Example 3 The only difference between the preparation method and Example 1 is that the grain boundary fusion agent used in S1 is a composite powder of Hf and Y without surface modification (Hf:Y mass ratio is 1:0.6, and the amount added is the same as in Example 1), which is directly added to the LF refining furnace without surface coating treatment steps; the process parameters and control logic of the remaining S2 to S6 are exactly the same as in Example 1.
[0036] Comparative Example 4 The only difference between the preparation method and Example 1 is that: no rare earth element cerium is added in S1, and the remaining components (including grain boundary fusion agent and composite microalloying agent) and dosage are the same as in Example 1; the process parameters and control logic of S2 to S6 are exactly the same as in Example 1.
[0037] Comparative Example 5 The only difference between the preparation method and Example 1 is that the modulus of the heat-generating and heat-insulating riser in S3 is 1.0 times (less than 1.2 times) of the maximum thermal section modulus of the valve body, and the top of the riser is covered with heat-insulating covering agent; the process parameters and control logic of the remaining S1, S2, S4 to S6 are exactly the same as those in Example 1.
[0038] Comparative Example 6 The only difference between the preparation method and Example 1 is that the multi-layer stepped bottom pouring system in S4 relies solely on the liquid level sensor to trigger the opening of each layer of horizontal sprue, without the K-type thermocouple temperature verification step. That is, when the liquid level reaches the blockage point, the horizontal sprue of that layer is opened immediately without steel liquid temperature comparison or waiting control. The process parameters and control logic of the remaining S1, S2, S3, S5, and S6 are exactly the same as those in Example 1.
[0039] Comparative Example 7 The only difference between the preparation method and Example 1 is that after casting in S5, the sand mold surface is covered with insulation cotton for natural slow cooling. After cooling to below 200°C, the mold is opened and the sand is cleaned. The differential gradient cooling step in the uniform temperature furnace is not performed, and the process directly enters the pre-hot cutting annealing process. The process parameters and control logic of the remaining S1, S2, S3, S4 and S6 are exactly the same as those in Example 1.
[0040] Comparative Example 8 The only difference between the preparation method and Example 1 is that in S5, after the casting is cooled to 180°C and the sand is removed, it is not reheated to 600-650°C for heat preservation and annealing, but the riser is cut directly with oxygen. The process parameters and control logic of the remaining S1, S2, S3, S4 and S6 are exactly the same as those of Example 1.
[0041] Comparative Example 9 The only difference between the preparation method and Example 1 is that: in S2, conformal external chills, side chills and anti-crack process tie rods are not set, and only heating and heat-insulating risers are used for feeding; the process parameters and control logic of the remaining S1, S3, S4, S5 and S6 are exactly the same as those of Example 1.
[0042] To verify the actual effects of the temperature-controlled casting process of the present invention in terms of hot crack resistance and casting density, the following experimental examples illustrate the temperature-controlled casting process provided by the present invention.
[0043] Experimental Example 1 Objective of the experimental group: To investigate the effect of grain boundary purification-microalloying synergistic treatment in step S1 on the hot cracking tendency of austenitic stainless steel valve castings, and to test the effectiveness of the present invention in grain boundary purification and grain boundary strengthening.
[0044] Experimental subjects: Experimental groups A, B, C, and D adopted the processes provided in Examples 1-4, respectively; Control group A adopted Comparative Example 1 (conventional bottom injection process); Control group B adopted Comparative Example 3 (unmodified grain boundary fusion agent, no surface coating treatment); Control group C adopted Comparative Example 4 (no rare earth element Ce added).
[0045] Test method: After each group completes the casting according to its own process, and the castings solidify and cool to room temperature, surface cracks are detected in the R-angle area connecting the valve body flange root and the cavity using dye penetrant testing (PT). The number of qualified castings in each group is counted, and the hot crack scrap rate is calculated using the following formula: Hot crack scrap rate = (Number of castings with surface cracks / Total number of castings in the group) × 100%. The number of castings counted in each group shall not be less than 20.
[0046]
[0047] According to Table 1 and Figure 2As shown, the hot cracking scrap rate of experimental group AD was 0%, while that of control group A was as high as 40%, control group B was 15%, and control group C was 10%. The experimental group used Hf and Y grain boundary fusion agent with surface coating modification added to the steel liquid at the end of refining. The coating layer delayed the release of active components, allowing them to participate in deoxidation and desulfurization reactions at high temperatures of 1580-1620℃. Hf and Y reacted with [O] and [S] dissolved in the steel liquid to form high-melting-point compounds and floated to the surface for removal, purifying the grain boundary region and preventing the low-melting-point eutectic phase from agglomerating at the grain boundary to form a liquid film at the end of solidification. At the same time, Nb-Ti composite microalloying formed dispersed carbonitride nucleation particles at the solidification front to refine the grains, and rare earth Ce agglomerated at the grain boundary to reduce the interfacial energy, thus eliminating the grain boundary weakening inducing factors from the material source. However, control group A did not undergo any grain boundary purification or microalloying treatment. During solidification, residual O, S, and impurity elements in the molten steel agglomerated towards the grain boundaries, forming a low-melting-point liquid phase. Under the action of solidification shrinkage stress, the liquid film at the grain boundaries was pulled apart, forming hot cracks. In control group B, because the grain boundary fusing agent was not surface modified, the Hf and Y active powder reacted with the O and S in the molten steel too early after being added to the molten steel. Most of them formed oxide inclusions inside the molten steel and could not be effectively floated and removed. At the same time, some active components were washed away by the molten steel, resulting in insufficient Hf and Y concentrations reaching the grain boundary region, reduced deoxidation and desulfurization efficiency, and incomplete grain boundary purification. In control group C, due to the lack of the grain boundary agglomeration strengthening effect of rare earth Ce, the grain boundary interface energy was high, and impurity elements were more likely to agglomerate towards the grain boundaries. The grain boundary bonding force was insufficient, resulting in the inability to effectively eliminate hot cracks.
[0048] Experimental Example 2 The objective of this experiment was to investigate the effect of the stepped pouring method, which combines liquid level triggering and temperature verification in step S4, on internal shrinkage defects in castings, and to test the effectiveness of this invention in terms of filling quality and feeding effect.
[0049] Experimental subjects: Experimental groups A, B, C, and D adopted the processes provided in Examples 1-4, respectively; Control group A adopted Comparative Example 1 (conventional single-layer bottom pouring); Control group B adopted Comparative Example 2 (CN106955994A temperature feedback stepped pouring, without liquid level sensor); Control group C adopted Comparative Example 5 (riser modulus < 1.2 times thermal modulus); Control group D adopted Comparative Example 6 (stepped pouring relies solely on liquid level triggering, without temperature verification).
[0050] Test Method: After solution treatment and cooling to room temperature, transverse samples with a thickness of 30 mm were cut from the hot spot area at the connection between the valve body flange root and the cavity using wire cutting. The cut surfaces of the samples were milled to a surface roughness Ra≤3.2μm before ultrasonic testing. A 5MHz straight probe was used for testing, with water as the coupling agent. The internal shrinkage defects of the samples were graded according to the MSSSP-54 standard (Class A: no detectable defects; Class B: scattered shrinkage cavities with a single diameter not exceeding 2 mm are allowed; Class C: continuous or densely distributed shrinkage cavities with a diameter exceeding 2 mm). One sample was taken from each casting, and 20 castings were counted from each group. The distribution of each grade was recorded, and the Class A pass rate was calculated using the following formula: Class A pass rate = (number of samples graded as Class A / total number of samples in the group) × 100%.
[0051]
[0052] According to Table 2 and Figure 3 As shown, the Class A pass rate of experimental groups AD reached over 85%, with experimental groups C and D reaching 95%; while the control group A had only 10%, control group B 30%, control group C 40%, and control group D 20%. All experimental groups exhibited excellent internal density, indicating that the present invention, through a dual feedback control logic triggered by a liquid level sensor and verified by a type K thermocouple, ensures that the ingate of each layer only opens when the molten steel temperature is within the preset threshold range of 1480-1510℃. This avoids the problems of premature injection of low-temperature molten steel forming a solidified shell that hinders feeding, and premature entry of high-temperature molten steel causing local overheating and exacerbating shrinkage differences. Simultaneously, the 1.2-modulus heating and insulating riser ensures unobstructed feeding channels in thicker areas, and the constraint of a molten steel surface rise speed of 10-15mm / s in the mold cavity allows the molten steel to fill the mold smoothly layer by layer from bottom to top, avoiding turbulent air entrapment. However, control group A, due to its single-layer bottom pouring method, experienced a long steel flow path and significant temperature drop, resulting in insufficient feeding power in thicker areas. Control group B, although employing temperature feedback control (CN106955994A), lacked a liquid level verification step, causing the temperature sensor to trigger ball dropping before the molten steel reached the blocking point, leading to premature sealing of the upper gating system and interruption of feeding. Control group C, with its riser modulus being only 1.0 times that of the thermal section modulus, had insufficient feeding capacity, resulting in inadequate compensation for solidification shrinkage in thick-walled areas. Control group D, lacking a temperature verification step, opened the gating system as soon as the liquid level was reached, leading to either excessively high actual molten steel temperature causing turbulent filling or insufficient feeding temperature causing inadequate feeding, all of which failed to achieve a dense internal quality in the casting.
[0053] Experimental Example 3 The objective of this experiment was to investigate the effects of gradient cooling and pre-hot cutting annealing in step S5 on the release of residual stress in castings and the cracking of risers during hot cutting, and to test the effectiveness of this invention in stress control.
[0054] Experimental objectives: Experimental groups A, B, C, and D adopted the processes provided in Examples 1-4, respectively; control group A adopted Comparative Example 1 (natural cooling to room temperature, without gradient cooling and annealing); control group B adopted Comparative Example 7 (no gradient cooling, only annealing); control group C adopted Comparative Example 8 (gradient cooling, without pre-hot cutting annealing).
[0055] Test Method: After the hot cutting of the riser was completed, the cut surface of the riser root was subjected to dye penetrant testing (PT). Castings with linear or circular cracks longer than 1.5 mm on the cut surface were identified as cracked castings. The number of castings with cracks in each group was counted, and the hot cutting crack rate was calculated using the following formula: Hot cutting crack rate = (Number of castings with cutting cracks / Total number of castings in the group) × 100%. At the same time, before the hot cutting of the riser, an X-ray residual stress analyzer (equipment model: ProtoiXRD, Cr target, tube voltage 25kV, tube current 4mA) was used to select three equally divided measuring points on the outer surface of the valve body flange root. The included angle between the measuring points was 120°. The residual stress was measured at each measuring point in both the axial and circumferential directions of the valve body. The arithmetic mean of the 6 test readings was taken as the surface residual stress value of the casting.
[0056]
[0057] According to Table 3 and Figure 4 As shown, the hot cutting crack rate of experimental group A and D was 0%, and the average residual stress was controlled below 52 MPa; while the hot cutting crack rate of control group A was as high as 60%, and the residual stress was 186 MPa; control group B was 30% and 112 MPa; control group C was 20% and 98 MPa. No hot cutting cracks appeared in any of the experimental groups, indicating that the present invention forms a complete stress control chain by deeply binding the two steps of gradient cooling and pre-hot cutting annealing: in the gradient cooling stage, the temperature difference between thick and thin walls is controlled within 80°C through forced air cooling in the thick-walled area and natural air cooling in the thin-walled area, so that the residual stress is initially homogenized inside the casting; after cooling to below 200°C in the furnace and opening the furnace, the casting is reheated to 600-650°C and held for 3-5 hours. At this time, the austenitic stainless steel is in the toughness temperature window, the atomic diffusion ability is enhanced, and the stress is fully relaxed and released; then it is slowly cooled to below 350°C in the furnace and then hot-cut. The temperature gradient in the hot cutting area is reduced, avoiding the secondary thermal stress impact caused by local high temperature heating during hot cutting. In contrast, control group A had neither gradient cooling nor annealing treatment, resulting in high residual stress in the castings, and thermal shock during hot cutting directly induced cracks; control group B had annealing but no gradient cooling, and the stress distribution caused by the temperature difference between thick and thin walls was extremely uneven, and annealing could not effectively eliminate local stress peaks; control group C had gradient cooling but lacked the annealing step, and the residual stress could not be fully relaxed and released, so hot cutting cracks were still not avoided.
[0058] Test Example 4 The purpose of this experiment is to investigate the effect of the complete process of this invention on the tensile strength and elongation of castings, and to test the effect of this invention on improving comprehensive mechanical properties.
[0059] Test subjects: Test groups A, B, C, and D adopted the processes provided in Examples 1-4, respectively; control group A adopted Comparative Example 1 (traditional process); control group B adopted Comparative Example 2 (CN106955994A temperature feedback stepped casting, no chills and tie rods and natural cooling); control group C adopted Comparative Example 9 (no conformal chills and crack-prevention tie rods).
[0060] Test method: After solution treatment of each group of castings, tensile test blanks were taken from the thick-walled area of the valve body along the center line of the wall thickness. The blanks were machined into round bar tensile test specimens with a gauge diameter of 10 mm and a gauge length of 50 mm according to ASTM E8 / E8M standards. Three specimens were taken from each group. The room temperature tensile test was performed using a microcomputer-controlled electronic universal testing machine. The force accuracy of the testing machine was ±0.5%, and the crossbeam displacement rate was set to 1 mm / min. The two ends of the specimen were centered and clamped in the testing machine fixture. The loading was started until the specimen broke. The tensile strength σb and elongation after fracture δ were automatically recorded by the testing machine control system. The arithmetic mean of the test results of the three specimens in each group was taken as the final value of the group.
[0061]
[0062] According to Table 4 and Figure 5 As shown, the tensile strength of experimental group AD was 485-520 MPa, and the elongation was 33%-40%; while the control group A was 450 MPa and 22%, control group B was 465 MPa and 26%, and control group C was 470 MPa and 24%. The tensile strength and elongation of the experimental group were significantly better than those of the control group, indicating that the synergistic effect of the complete process of this invention from the material source to temperature-controlled casting to stress regulation not only eliminated hot cracks and shrinkage defects, but also improved the comprehensive mechanical properties of the casting through grain refinement. Control group A had the worst mechanical properties due to the coexistence of hot cracks and shrinkage defects; although control group B adopted the temperature feedback stepped casting method of CN106955994A, the lack of chill tie structure led to the concentration of shrinkage stress in the thick and thin walls during solidification, resulting in internal shrinkage defects and limited elongation; control group C lacked conformal chills and tie rods, resulting in insufficient feeding in the thick-walled area and ineffective dispersion of stress concentration, thus limiting performance improvement. The results of Experiments 1-4 collectively demonstrate that the present invention, through a complete chain of grain boundary purification-microalloying synergistic treatment, liquid level-temperature dual feedback stepped casting, gradient cooling and pre-hot cutting annealing stress control, eliminates the causes of hot cracking from the material's intrinsic layer, optimizes the density from the filling layer, and eliminates the hidden danger of cracking from the stress layer, thereby achieving a synergistic improvement in the hot cracking resistance and mechanical properties of austenitic stainless steel valve castings.
[0063] In summary, the four experimental examples demonstrate that this invention eliminates the root cause of grain boundary weakening through synergistic grain boundary purification and microalloying treatment (Example 1), optimizes filling quality and feeding effect through dual-feedback step casting based on liquid level and temperature (Example 2), and eliminates the risk of hot cutting cracks through continuous stress control via gradient cooling and pre-hot cutting annealing (Example 3). Ultimately, the tensile strength and elongation of the casting are improved (Example 4). This proves that the complete technical chain of this invention, from the material source to casting control to stress control, can synergistically solve the hot cracking problem caused by large wall thickness differences and high linear expansion coefficient in austenitic stainless steel valve castings, and has made progress in both hot crack resistance and comprehensive mechanical properties.
[0064] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A temperature-controlled casting process for a thermally crack-resistant stainless steel valve body, characterized in that, Includes the following steps: S1. Prepare austenitic stainless steel scrap and alloy furnace charge, melt them in an electric arc furnace, transfer them to an LF refining furnace, use low-sulfur covering slag and bottom-blown argon to stir for deep desulfurization, so that the sulfur content of the molten steel is ≤0.003%. Then, at the end of the refining process, add a modified grain boundary fusing agent, heat to 1580-1620℃ and hold for 5-8 minutes, then add a composite microalloying agent and rare earth elements, stir evenly with bottom-blown argon and tap the steel to obtain molten steel with synergistic treatment of grain boundary purification and microalloying. S2. Based on the location and size of the hot spot obtained from the solidification simulation of the three-dimensional model of the valve body, conformal external chills are set on the outer side of the cavity corresponding to the flange root and the thick part of the valve seat, and side chills are set between adjacent insulation risers. Anti-crack process tie rods are added at the corners where the wall thickness changes abruptly. Furan resin sand molding is then used, and the cavity surface is coated with alcohol-based zircon powder coating containing nano-zirconia micro powder. Thermocouple mounting holes are reserved on the side of the blockage point of each layer of the vertical runner. S3. After primary refining in an electric arc furnace, the treated molten steel is transferred to an LF refining furnace and tapped at a temperature of 1600-1630℃ and then transferred to a ladle. During the tapping process, a final deoxidizer is added with the steel stream to perform final deoxidation, so that the hydrogen content of the molten steel is ≤2ppm. A foam ceramic filter is installed in the horizontal runner at a distance of 150-200mm from the center line of the vertical runner to obtain pure molten steel to enter the mold cavity. S4. A multi-layer stepped bottom pouring system is adopted for layered pouring. Ceramic plugs and feedback execution components consisting of liquid level sensors, K-type thermocouples and electric push rods are installed at the entrance of each layer's horizontal pouring channel. S5. After pouring, cover the sand mold surface with insulation cotton for slow cooling. Then transfer the casting along with the sand mold into the uniform temperature furnace. Use a differentiated gradient cooling method that combines forced air cooling by variable frequency fan in the thick-walled area with natural air cooling in the thin-walled area. After cooling, open the mold, clean the sand, put it back into the furnace for annealing, and then cool it with the furnace to the appropriate temperature before hot cutting. S6. After hot cutting the riser, the casting is placed into a heat treatment furnace and heated to 1040-1100℃ at a heating rate of ≤200℃ / h and held at that temperature. Then it is transferred to circulating water for water quenching, and the ferrite content is 4-15%, to obtain valve steel castings with resistance to hot cracking and corrosion.
2. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In S1, the amount of composite microalloying agent added is 0.15-0.40 wt%; the amount of rare earth element added is 0.3-0.5 wt%; the amount of surface-modified grain boundary fusion agent added is 0.05-0.15 wt%; and the balance is austenitic stainless steel scrap and alloy furnace charge.
3. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 2, characterized in that, The mass ratio of niobium to titanium in the composite microalloying agent is 8-12:1; the rare earth element is selected from cerium or lanthanum.
4. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In step S1, the modification of the grain boundary fusion agent includes the following steps: Hafnium and yttrium powders were mixed at a mass ratio of 1:0.5-0.8 and then added to a polyvinyl alcohol aqueous solution. The mixture was stirred at 200-400 r / min for 40-60 min in a constant temperature water bath at 60-80℃ to uniformly coat the powder surface with a polyvinyl alcohol pre-coating. Subsequently, sodium alginate solution was added and the pH was adjusted to 4.5-5.
5. After centrifugation, the mixture was dried at 80-100℃ for 2-4 h to obtain grain boundary fusion agent particles with a core-shell structure.
5. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In S2, the thickness of the conformal external chill is 0.6-1.0 times the wall thickness of the corresponding hot section, and it is made of gray cast iron or chromite refractory material. A 2-5mm chromite sand buffer layer is placed between the chill and the mold cavity surface. The cross-section of the anti-crack process tie rod is rectangular, the thickness is 0.6-0.8 times the wall thickness of the cavity, and the width of the tie rod is ≥15mm.
6. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In S2, the nano-zirconia powder in the alcohol-based zircon powder coating accounts for 3-5% of the total mass of the coating, the particle size of the nano-zirconia powder is not greater than 50nm, the coating thickness is 0.3-0.5mm and it is dried by ignition.
7. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In S3, the heat-insulating riser is a heat-generating heat-insulating riser with a riser modulus ≥ the maximum thermal section modulus of the valve body × 1.2, and the top of the riser is covered with a heat-insulating covering agent; the thickness of the foam ceramic filter is 15-20mm and the pore density is 15-20ppi.
8. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In step S4, the opening control of each horizontal runner of the multi-layer stepped bottom pouring system includes the following steps: Molten steel is continuously injected into the mold cavity from the bottom inner gating channel, and the molten steel level in the vertical gating channel rises accordingly. When the liquid level sensor detects that the liquid level has risen to the blockage point of the upper horizontal gating channel, the PLC controller reads the real-time temperature value of the K-type thermocouple at the blockage point and compares it with the preset threshold range of 1480-1510℃. If the measured temperature is within the threshold range, the PLC controller sends an opening command to the corresponding electric push rod, which drives the ceramic ball to exit the horizontal runner inlet, and the horizontal runner of that layer opens. If the measured temperature is higher than the upper limit of the threshold, the PLC controller postpones sending the opening command, the electric push rod keeps the ceramic ball in the horizontal runner inlet closed, and the molten steel continues to be injected into the cavity through the lower layer of the already opened ingate. The horizontal runner of that layer will be opened again after the molten steel in the vertical runner cools down to within the threshold range due to heat dissipation. The opening timing of each layer of horizontal runner is controlled independently according to the above logic, and the measured temperature difference between two adjacent layers when they are opened is ≤25℃. By controlling the opening sequence and timing of the above-mentioned layer-by-layer opening, the rising speed of the molten steel surface in the cavity is kept at 10-15 mm / s, and the pouring temperature is kept at 1450-1480℃.
9. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, In S5, the insulation cotton covering thickness is based on 1 hour of insulation for every 25mm of casting wall thickness, so that the casting inside the mold is slowly cooled to 550-650℃ before entering the uniform temperature furnace; during the differential gradient cooling process, the temperature difference between the thick and thin wall areas is collected every 30 seconds and the operation of the variable frequency fan is dynamically adjusted accordingly to ensure that the instantaneous temperature difference between the thick and thin wall areas is ≤80℃; before opening the mold, the casting is cooled to below 200℃ with the mold, cleaned of sand, and then reheated in the furnace to 600-650℃ for insulation, and then slowly cooled to below 350℃ with the furnace before being taken out for hot cutting of risers.
10. The temperature-controlled casting process for the anti-crack stainless steel valve body according to claim 1, characterized in that, The temperature-controlled casting process is applicable to the casting production of gate valve bodies made of ASTM A351 standard CF8, CF8M, CF3 or CF3M austenitic stainless steel with diameters from DN100 to DN400.
Citation Information
Patent Citations
Temperature-controlled type stepped pouring method and stepped pouring device of casting pieces
CN106955994A